Development of whole sporozoite malaria vaccines - Michael R. Hollingdale; Martha Sedegah (Taylor & Francis Group, 2017)
Introduction: Despite recent advances, malaria remains a major health threat both to populations in endemic areas as well travelers, including military personnel, to these areas. Subunit vaccines have not yet achieved sufficient efficacy needed for use in any of these at risk populations. Areas covered: This review discusses the current status of various whole sporozoite vaccine approaches and is mainly focused on current clinical trials. Expert commentary: Nearly 100% efficacy was achieved by administering multiple bites of radiation-attenuated sporozoite (RAS) Plasmodium falciparum-infected mosquitoes; this is impractical for widespread use. Now, this high level efficacy has been reproduced using purified, metabolically active RAS (PfSPZ Sanaria® Vaccine), which is undergoing extensive clinical testing. Alternative whole sporozoite vaccines include immunization with fully infectious sporozoites under chloroquine prophylaxis (CPS) or as genetically-attenuated parasites (GAP). By also manufacturing purified infectious sporozoites, it is now possible to combine these with CPS and GAP, as well as perform challenge studies using controlled doses of sporozoites.